Illness perception of the patients with hematological cancers: A single center study - ELİF GÜLLÜ ÇALIŞKAN and KEZİBAN ŞEN and ALPARSLAN MERDİN and MEHMET SİNAN DAL and; İ ALTUNTAŞ (International Journal of Pharma and Bio Sciences, 2019)
The beliefs and cognitive evaluations of patients about their disease are called illness perception. Patients’ knowledge, comments, perceptions, beliefs, and evaluations about the illness are the factors that determine the psychosocial reactions in the cancer process. Severe anemia, deep neutropenia and thrombocytopenia, mucositis, fatigue, asthenia, susceptibility to bleeding, nausea and vomiting, as well as changes in body image, may severely impair quality of life and psychosocial life in hematologic cancer patients. The relatively poor prognosis of hematological cancers and long-term chemotherapy treatments could be a challenging process for individuals with hematological cancer. In this study, it was aimed to determine the disease perceptions of the patients with hematological cancers. The research was a descriptive study. The study included 80 inpatient unit patients admitted to the hematology clinic between October 2017 and April 2018. It was determined that 42.6% of the patients involved in the study were diagnosed with acute leukemia and 61.2% of the patients were diagnosed with the disease in less than 6 months. The most common disease symptoms were reported as power loss (86.3%), fatigue (85%), sleep problems (60%). Psychological references (stress or anxiety, family problems, personality traits) were stated as the main cause of illness by the patients. Patients with hematological cancer had negative emotional conditions related to their disease. Patients believe that their illnesses affect their physical, psychological and social functions.